Mediator role of resilience in the relationship between neuroticism and psychological symptoms: COVID-19 Pandemic and supermarket employees - Civgin, Umut; Yorulmaz, Elcin; Yazar, Kemal (Springer, 2023)
The current research aimed to examine the relationship between personality traits, resilience, and psychological symptom levels of front-line supermarket employees during the COVID-19 pandemic. Three-hundred and ten (310) supermarket employees participated in the research between March and May 2021. Participants filled out the questionnaire sets online The Demographic Information Form, Symptom Checklist, Five Factor Inventory and Resilience Scale for Adults were presented as questionnaire sets. Pearson Correlation Analyses were conducted to determine the relationships between variables, Multiple Regression and mediation analyses were conducted to discover the predictors of symptom level. It was found that personality traits, resilience and psychological symptom levels are related to each other. Conscientiousness, neuroticism, openness and resilience are significant predictors of psychological symptom level. In addition, resilience plays a mediating role in the relationship between neuroticism and psychological symptom levels. The findings were discussed within the framework of the relevant literature and COVID-19 research findings.
Keywords: COVID-19; Resilience; Psychological symptom; Neuroticism